2001
DOI: 10.1054/bjoc.2000.1590
|View full text |Cite
|
Sign up to set email alerts
|

The adhesion molecule CD44v6 is associated with a high risk for local recurrence in adult soft tissue sarcomas

Abstract: Summary In many malignant diseases the expression levels of CD44 and its splice variant v6 (CD44v6) have been associated with the prognosis. The purpose of this study was to investigate the clinical significance of CD44 in adult soft tissue sarcomas (STS). 133 STS patients with a limb or superficial trunk tumour treated at the Helsinki University Central Hospital in 1987-1993 with a median follow-up time of 68 months were included in this study. The expression of CD44 and CD44v6 was determined immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
4
15
0
1
Order By: Relevance
“…These levels were similar to those previously reported, although comparisons are difficult, since the methods of assessment, and the cut-off levels differ [83,108,135]. A high CD44 expression was also a strong prognostic factor for metastasis in our series of 140 mixed STS with a HR of 2.4, but not in the series of 201 MFH (Table 17).…”
Section: Cd44supporting
confidence: 88%
See 4 more Smart Citations
“…These levels were similar to those previously reported, although comparisons are difficult, since the methods of assessment, and the cut-off levels differ [83,108,135]. A high CD44 expression was also a strong prognostic factor for metastasis in our series of 140 mixed STS with a HR of 2.4, but not in the series of 201 MFH (Table 17).…”
Section: Cd44supporting
confidence: 88%
“…In a series of 47 STS, Kahara et al [83] demonstrated that most sarcomas expressed CD44s, but that the isoform CD44v6 was more commonly expressed in high-grade tumors, and this isoform was also correlated to a shorter metastasis-free survival. Also Maula et al [108] found that high CD44s expression, and particularly the isoform CD44v6 was associated with an increased risk of LR, but not with survival.…”
Section: Cd44mentioning
confidence: 99%
See 3 more Smart Citations